The lost taxon Phalaena phadima Stoll, 1782, recognized as Megalopygidae (Insecta: Lepidoptera) - Becker, Vitor O. (SHILAP Revista de lepidopterología, 2023)
The identity and taxonomic placement of Phalaena phadima Stoll, 1782 is established and removed from Prorifrons Barnes & McDunnough, 1911 (Lasiocampidae) to Megalopyge Hübner, [1820] (Megalopygidae), as the senior synonym of Hydrias lecca Druce, 1890, syn. nov.